An ex ante economic and policy analysis of biotechnology research for livestock disease resistance: Trypanosomosis in Africa - Falconi, César A.; Omamo, Steven Were; d'Ieteren, Guy (International Service for National Agricultural Research, 1999)
A range of diseases seriously constrains livestock development in Africa. Among these diseases, trypanosomosis is the most important. Annual direct and indirect losses from trypanosomosis have been estimated at over $5 billion. Conventional control options are either unavailable (e.g., vaccines), expensive (e.g., chemotherapy), or difficult to implement effectively (e.g., vector suppression). There is thus great interest in understanding and exploiting the inherited resistance to trypanosomosis of some livestock species. This paper undertakes an ex-ante economic analysis of biotechnology research on how disease resistance in trypanotolerant breeds can be maintained while enhancing characteristics of economic importance to farmers, and on how trypanotolerance can be conferred to susceptible animals while retaining their other important traits. The results indicate that benefits to research are more than five times costs and that the internal rate of return is more than double the real interest rate. However, these returns hinge on maintaining current levels of human resource allocations and strategic but relatively small capital investments. The results also suggest that further research is needed to consistently identify and track the impacts of alternative intellectual property rights options on the levels and distributions of biotechnology research benefits.